The Influence of Organizational Culture and Organizational Commitment on Managerial Performance at KPPBC TMP A Pasuruan - Basith, Heryaas; Sundjoto, Sundjoto; Rahayu, Sri; Fitrianty, Rifda (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Effective employee performance is central to organizational success, as it determines an institution’s ability to meet objectives efficiently and maintain competitive advantages. This research examines the role of organizational culture and employee commitment in shaping managerial performance at KPPBC TMP A Pasuruan, a critical Indonesian customs and excise office operating under stringent regulatory and bureaucratic structures. Employing a quantitative methodology, the study targeted the full population of 119 employees, selecting 66 respondents via simple random sampling to ensure proportional representation and mitigate sampling bias. Data were collected through structured Likert-scale questionnaires validated for reliability and construct accuracy, measuring perceptions of organizational culture, commitment, and managerial performance. Multiple linear regression analysis using SPSS allowed the evaluation of both individual and joint effects of the independent variables. Results indicate that organizational culture and commitment both have significant positive impacts on managerial performance, both separately and in combination, accounting for a substantial proportion of performance variation. Strong organizational culture instills shared values, norms, and behavioral guidance that facilitate strategic decision-making, creativity, and operational efficiency. Simultaneously, committed employees exhibit greater emotional attachment, responsibility, and motivation, resulting in improved managerial effectiveness. These findings suggest that the integration of cultural alignment and employee commitment is critical in cultivating a supportive, high-performance managerial environment. For practitioners and leaders, the study underscores the importance of fostering a strong organizational culture alongside promoting employee dedication, which together enhance managerial capability, organizational outcomes, and the development of a disciplined, accountable, and performance-oriented workforce.